Terrorism formation with supranational character: kosmopolitization factor - V. I. Dolgy (Vestnik MGIMO-Universiteta)
The article indicates the general trends leading to the transformation of contemporary terrorism from national to transnational stage, above all the global role of the cosmopolitization. It contains a collative analyses of the two types of terrorism. One of them, existing at the age of industrial modernity, and another one corresponds to the contemporary societies.